Synthesis of copper catalysts for click chemistry from distillery wastewater using magnetically recoverable bionanoparticles. Issue 15 (8th July 2019) - Kimber, Richard L.; Parmeggiani, Fabio; Joshi, Nimisha; Rakowski, Alexander M.; Haigh, Sarah J.; Turner, Nicholas J.; Lloyd, Jonathan R.
Abstract : Biogenic magnetite nanoparticles were employed to recover copper from whisky distillery wastewaters, generating an efficient and reusable click chemistry catalyst. Abstract : Copper recovered from a whisky distillery waste stream is shown to be an effective catalyst for a range of azide–alkyne "click" reactions. Biogenic nanomagnetite (BNM), produced under mild conditions, was used to rapidly recover and subsequently support the Cu catalyst which could be separated and recycled easily.